PELATIHAN PENGGUNAAN APLIKASI BUKU WARUNG SEBAGAI MEDIA PEMBUKUAN KEUANGAN DIGITAL BAGI UMKM - Ridho, Muhammad; Pujihastuti, Isti; Rofieq, Ainur (Universitas Islam 45 Bekasi, 2023)
MSMEs make a large contribution to the national economy, but this is not matched by access to digital financial services. Current technological developments enable MSMEs to run their businesses easily, effectively, and efficiently. One of the conveniences that can be felt is the ease of making financial books for your business using the application so that financial recording and calculations can be carried out very easily. However, many MSME players are not yet aware of the importance of financial bookkeeping and digital financial bookkeeping through applications. A similar thing also happened to MSMEs in Karanghaur village, Pebayuran subdistrict. Starting from the problems that arise, namely a lack of understanding regarding the importance of financial bookkeeping for MSMEs and understanding about the use of digital financial bookkeeping applications. The method that will be applied in this activity is bookkeeping training for MSMEs. So it is hoped that the program